FDG PET/CT of Primary Breast Lymphoma in a Man. (10th May 2022) - Ran, Pengcheng; Li, Hui; Hu, Yongzhen; Chen, Miao; Dong, Aisheng
Abstract: Primary lymphoma of the male breast is extremely rare. We describe FDG PET/CT findings in a man with primary breast lymphoma in his right breast. The breast tumor showed intense FDG uptake mimicking breast carcinoma.